Connecting the ISM to TeV PWNe and PWN candidates. (10th April 2019) - Voisin, F. J.; Rowell, G. P.; Burton, M. G.; Fukui, Y.; Sano, H.; Aharonian, F.; Maxted, N.; Braiding, C.; Blackwell, R.; Lau, J.
Abstract: We investigate the interstellar medium towards seven TeV gamma-ray sources thought to be pulsar wind nebulae using Mopra molecular line observations at 7 mm [CS(1–0), SiO(1–0, v = 0)], Nanten CO(1–0) data and the Southern Galactic Plane Survey/GASS Hi survey. We have discovered several dense molecular clouds co-located to these TeV gamma-ray sources, which allows us to search for cosmic rays coming from progenitor SNRs or, potentially, from pulsar wind nebulae. We notably found SiO(1–0, v = 0) emission towards HESS J1809–193, highlighting possible interaction between the adjacent supernova remnant SNR G011.0–0.0 and the molecular cloud at d ∼ 3.7 kpc. Using morphological features, and comparative studies of our column densities with those obtained from X-ray measurements, we claim a distance d ∼ 8.6 − 9.7kpc for SNR G292.2–00.5, d ∼ 3.5 − 5.6 kpc for PSR J1418–6058 and d ∼ 1.5 kpc for the new SNR candidate found towards HESS J1303–631. From our mass and density estimates of selected molecular clouds, we discuss signatures of hadronic/leptonic components from pulsar wind nebulae and their progenitor SNRs. Interestingly, the molecular gas, which overlaps HESS J1026–582 at d ∼ 5 kpc, may support a hadronic origin. We find however that this scenario requires an undetected cosmic-ray accelerator to be located at d < 10 pc from the molecular cloud. For HESS J1809–193, the cosmic rays which have escaped SNR G011.0–0.0 could contribute to the TeV gamma-ray emission. Finally, from the hypothesis that at most 20% the pulsar spin down power could be converted into CRs, we find that among the studied pulsar wind nebulae, only those from PSR J1809–1917 could potentially contribute to the TeV emission.